Impact of Collagen Membrane in Vertical Ridge Augmentation Using Ti‐Reinforced PTFE Mesh: A Randomised Controlled Trial. - Urban, Istvan A.; Serroni, Matteo; Dias, Debora R.; Baráth, Zoltán; Forster, Andras; Araújo, Tiago G.; Saleh, Muhammad H. A.; Cucchi, Alessandro; Ravidà, Andrea (Journal of Clinical Periodontology, 2025)
Aims: This non‐inferiority randomised clinical trial aimed to compare vertical bone gain (VBG), volumetric bone changes and incidence of complications after vertical ridge augmentation (VRA) using perforated titanium‐reinforced dense‐polytetrafluoroethylene (PTFE) mesh covered by a collagen membrane (CM) or used alone. Materials and Methods: Thirty patients with vertical bone defects were randomly assigned to receive VRA with either PTFE + CM or PTFE alone. Meshes were removed after 9 months. Clinical assessments included complication rates, pseudo‐periosteum type and bone density. VBG, effective regeneration rate and the need for additional augmentation were evaluated using CBCT reconstructions. Results: Non‐inferiority of PTFE alone compared with PTFE + CM was not demonstrated for absolute and relative VBG (4.5 ± 2.1 mm vs. 4.1 ± 2.7 mm, 79.2% ± 16.6% vs. 85.8% ± 10.6%, respectively), effective regeneration rates (69.3% ± 17.9% vs. 72.3% ± 16.4%, respectively) or complication rates (6.7% in both groups). A higher incidence of type 1 pseudo‐periosteum was observed in the PTFE + CM group. Conclusion: The non‐inferiority of PTFE alone compared with PTFE + CM for absolute VBG was not established. However, both techniques led to comparable outcomes for VBG, complication rates and bone density. The higher incidence of type 1 pseudo‐periosteum and lacking bone volume in the PTFE + CM group suggests that adding a collagen membrane may help prevent soft tissue ingrowth. Trial Registration:Clinicaltrials.gov identification number: NCT04843488